New pathogenic germline variants identified in mesothelioma. (May 2023) - Belcaid, Laila; Bertelsen, Birgitte; Wadt, Karin; Tuxen, Ida; Spanggaard, Iben; Højgaard, Martin; Benn Sørensen, Jens; Ravn, Jesper; Lassen, Ulrik; Cilius Nielsen, Finn; Rohrberg, Kristoffer; Westmose Yde, Christina
Highlights: High frequency of germline pathogenic variants in patients with mesothelioma. Identification of two germline pathogenic variants not previously reported in mesothelioma. Germline testing in patients with mesothelioma may be indicated. Homologous recombination pathway should be further investigated as a potential target for mesothelioma. Abstract: Background: Mesothelioma (MM) is associated with asbestos exposure, tumor heterogeneity and aggressive clinical behavior. Identification of germline pathogenic variants (PVs) in mesothelioma is relevant for identifying potential actionable targets and genetic counseling. Methods: 44 patients underwent whole exome sequencing (WES) or whole genome sequencing (WGS). Germline variants were selected according to association with inherited cancer using a 168-gene in silico panel, and variants classified according to ACMG/AMP classification as pathogenic (class 5) or likely pathogenic (class 4). Results: In total, 16 patients (36%) were found to carry pathogenic or likely pathogenic variants in 13 cancer associated genes ( ATM, BAP1, BRCA2, CDKN2A, FANCA, FANCC, FANCD2, FANCM, MUTYH, NBN, RAD51B, SDHA and XPC ). The germline PVs occurred in DNA repair pathways, including homologous recombination repair (HRR) (75%), nucleotide excision repair (6%), cell cycle regulatory (7%), base excision repair (6%), and hypoxic pathway (6%). Five (31%) patients with a germline PV had a first or second degree relative with mesothelioma compared to none for patients without a germline PV. Previously undiagnosed BRCA2 germline PVs were identified in two patients. Potential actionable targets based on the germline PVs were found in four patients (9%). Conclusion: This study revealed a high frequency of germline PVs in patients with mesothelioma. Furthermore, we identified germline PVs in two genes ( NBN & RAD51B ) not previously associated with mesothelioma. The data support germline testing in mesothelioma and provide a rationale for additional investigation of the HRR pathway as a potential actionable target.